A novel elicitor protein phosphopentomutase from Bacillus velezensis LJ02 enhances tomato resistance to Botrytis cinerea - Li, Zhuoran; Hu, Jianan; Sun, Qi; Zhang, Xi; Chang, Ruokui; Wang, Yuanhong (Frontiers in Plant Science, 2022)
The loss of tomatoes caused by Botrytis cinerea (B. cinerea) is one of the crucial issues restricting the tomato yield. This study screened the elicitor protein phosphopentomutase from Bacillus velezensis LJ02 (BvEP) which improves the tomato resistance to B. cinerea. Phosphatemutase was reported to play a crucial role in the nucleoside synthesis of various microorganisms. However, there is no report on improving plant resistance by phosphopentomutase, and the related signaling pathway in the immune response has not been elucidated. High purity recombinant BvEP protein have no direct inhibitory effect on B. cinerea in vitro,and but induce the hypersensitivity response (HR) in Nicotiana tabacum. Tomato leaves overexpressing BvEP were found to be significantly more resistant to B. cinerea by Agrobacterium-mediated genetic transformation. Several defense genes, including WRKY28 and PTI5 of PAMP-triggered immunity (PTI), UDP and UDP1 of effector-triggered immunity (ETI), Hin1 and HSR203J of HR, PR1a of systemic acquired resistance (SAR) and the SAR related gene NPR1 were all up-regulated in transgenic tomato leaves overexpressing BvEP. In addition, it was found that transient overexpression of BvEP reduced the rot rate and lesion diameter of tomato fruits caused by B. cinerea, and increased the expression of PTI, ETI, SAR-related genes, ROS content, SOD and POD activities in tomato fruits, while there was no significant effect on the weight loss and TSS, TA and Vc contents of tomato fruits. This study provides new insights into innovative breeding of tomato disease resistance and has great significance for loss reduction and income enhancement in the tomato industry.